Sex Workers' Religiousity and Faith in God: Case Study on “Ayam Kampus” in East Java, Indonesia - Rijal, Syamsul; El-Rumi, Umiarso (KALAM, 2018)
Prostitution is often called to be a social disease that is far from anchoring the values of religiousness, especially diversity. It is normal if the stigma of tilting towards sex workers arises from insults, mocks, until the behavior of ignorance shown by the clergy. Even though sex workers are outside the circle of prostitution, they are "giddy" looking for life's meaning in the form of religious feelings in which there is a sense of divinity. Therefore, this article tries to understand the reality of religion - in which there are also emerging of sex workers. The reality is analyzed using the theory of dramaturgy which divides prostitution into the front stage (the practice of prostitution) and the rear stage (the privacy of sex workers). This article uses a qualitative approach to the type of phenomenology that portrays the practice of ayam kampus prostitution in East Java. Data collection used in-depth interviews and participant observation; Data analysis used the interactive models of Miles and Hubermann. This research found that the front stage of the practice of prostitution has never been friendly with the presence of God, especially to express its diversity. But, on the back stage, they can expose themselves in their religiosity and divinity with full serenity and appreciation. The conclusions of this research is the religiosity practiced by sex workers is separated from the normative symbol of religion, while God is immersed tightly in their soul and God is present in the most subjective and impersonal form in him.